2015
DOI: 10.1016/j.jtusci.2014.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of iodo polyurethane foam and its application in removing of aniline blue and crystal violet from laundry wastewater

Abstract: A new sorbent was prepared by treating polyurethane foam with HCl and replacing the amino functional groups with iodine atoms. The properties of iodo-polyurethane were studied with infrared, ultraviolet and visible spectroscopy, bulk density, pH ZPC and elemental and thermal analysis. Removal of aniline blue and crystal violet dyes from water with iodo-polyurethane were investigated with the batch technique. Maximum removal was achieved at pH 7-12. The effect of the initial dye concentration on the equilibrium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 32 publications
0
27
0
Order By: Relevance
“…The second step of film diffusion follows the pseudo‐first‐order kinetics, while intraparticle diffusion does not. At longer times, the adsorption process changes and the experimental data did not fit the pseudo‐first‐order equation, so pseudo‐second‐order kinetics model was applied: tqt=1K2qe2+1qet where the concentration of CV adsorbed at equilibrium and at time t is q e and q t (mol g −1 ), respectively, and K 2 is the pseudo‐second‐order rate constant (Moawed, Abulkibash, & El‐Shahat, ). If adsorption process follows the pseudo‐second order, a linear relationship is obtained between t / q t and t (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The second step of film diffusion follows the pseudo‐first‐order kinetics, while intraparticle diffusion does not. At longer times, the adsorption process changes and the experimental data did not fit the pseudo‐first‐order equation, so pseudo‐second‐order kinetics model was applied: tqt=1K2qe2+1qet where the concentration of CV adsorbed at equilibrium and at time t is q e and q t (mol g −1 ), respectively, and K 2 is the pseudo‐second‐order rate constant (Moawed, Abulkibash, & El‐Shahat, ). If adsorption process follows the pseudo‐second order, a linear relationship is obtained between t / q t and t (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that if the plot of q t against t 1/2 (Fig. ) fits a straight line, intraparticle diffusion process is the rate controlling step of adsorption process (Table ) (Moawed et al, ; Wu, Tseng, & Juang, ). If the kinetic data fit this linear relationship, the slope could be used to obtain the rate constant for intraparticle transport using the following equation: 0.25emqt=Kdt1/2+C where the amount of CV sorbed at time t (min) is q t (mol g −1 ), the rate constant of intraparticle transport is K d (mol gmin −1/2 ) and the intercept is C (mg g −1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the foam could be regenerated many times without obvious decrease in the absorption capacity . In order to enhance the adsorption selectivity and efficiency for removal of organic dye from wastewater, Ke et al synthesized an attapulgite‐modified PU foam by the foaming technique . Attapulgite, as a natural adsorbent with high surface area and exchangeable cations, as well as reactive hydroxyl on its surface, can effectively absorb cations dyes from wastewater.…”
Section: Adsorbent Materialsmentioning
confidence: 99%